Liquid-liquid-gas stratified fractional model flow: I. Model in two parallel plates. Issue 1 (31st December 2016) - Suárez-Domínguez, E.J.; Alarcón-Montelongo, I.S.; Rodríguez-Valdés, A.; Palacio-Pérez, A.; Izquierdo-Kulich, E.F.
Abstract: Three phase fluid flow is a crucial subject in many industries such as chemical, oil and gas. Actually, software and empirical predictions exist for pressure drop in liquid-liquid or liquid-gas stratified flow but liquid-liquid-gas flow is not well known. Simple prediction of pressure gradient in three phase flow will lead to decisions and the use or not of robust methods for a better design of an energy efficient transportation system. This paper presents a solution for the velocity profile and pressure drop for liquid-liquid-gas flow applied in parallel plates. Also, by using fractional calculus, we show a method to determine the pressure drop in liquid-liquid-gas systems, which allows us to consider the effect of flow regime on velocity profile and pressure drop. We also propose a relationship to determine the order of fractional derivatives. This is related to the Reynolds number corresponding to each phase, which is found flowing at the specified volumetric speed. The solved unified model is useful for laminar, transient of turbulent flow.